Rational dosing of gabapentin and pregabalin in chronic kidney disease - Raouf M; Atkinson TJ; Crumb MW; Fudin J (Journal of Pain Research, 2017)
Mena Raouf,1 Timothy J Atkinson,1 Meredith W Crumb,1 Jeffrey Fudin2–5 1VA Tennessee Valley Healthcare System, Murfreesboro, Nashville, TN, 2Stratton VA Medical Center, 3Albany College of Pharmacy and Health Sciences, Albany, NY, 4Western New England University College of Pharmacy, Springfield, MA, 5Scientific and Clinical Affairs, Remitigate LLC, Delmar, NY, USA IntroductionRenal dose adjustments for gabapentin and pregabalin are ubiquitously evident in the medical literature. All manufacturers for these branded and generic dosage forms list dosing recommendations relative to creatinine clearance (CrCl) for both medications (Table 1).1,2 However, the basis of these recommendations has not been well articulated.